2010
DOI: 10.1007/s11910-010-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Dementia

Abstract: Dementia associated with Parkinson's disease (PDD) is a common problem and one that is associated with significant morbidity and mortality. Over the past decade, increasing research efforts and funding have been directed toward an improved understanding of PDD. Despite these efforts, fundamental gaps remain in our knowledge. Consequently, therapeutic progress has been frustratingly slow and incomplete. To significantly affect PDD, novel "disease-modifying" agents, rather than more traditional neurotransmitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…There have been reports of a general reduction in visuospatial perception in patients with PDD. 37,38 Diffusion impairment in the posterior cingulum bundle may reflect the particular pathophysiology of PDD.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of a general reduction in visuospatial perception in patients with PDD. 37,38 Diffusion impairment in the posterior cingulum bundle may reflect the particular pathophysiology of PDD.…”
Section: Discussionmentioning
confidence: 99%
“…Although PD has been classically associated with psychiatric comorbidities such as dementia [2] and psychosis [3], recent studies have shown that patients with PD can develop a variety of behavioral problems associated with impulse dyscontrol, including pathological gambling, hypersexuality, punding (repetitive purposeless motor acts not distressing to the patient), and compulsive shopping and eating [4]. These pathological behaviors are currently classified as impulse control disorders (ICDs) and exert negative consequences in terms of the patients' health-related quality of life, mainly because of the interference with their social functioning [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of mice have been generated to reproduce the predominantly subcortical pathology associated with PD, which according to the Braak staging, starts in the olfactory bulb and ventral medulla, then progressively include raphe, locus coeruleus, and subsequently substantia nigra, basal nucleus of Meynert and amygdala, before invading the cerebral cortex at the latest stages of disease [58,59]. As discussed earlier, this pattern of ␣-syn pathology is compatible with the progressive nature of cognitive deficits in PD, that consists of subtle impairments in executive function and attention at early stages of the disease [16,17] and only evolve toward frank dementia at later stages in a subset of patients [18,19]. Furthermore, the cognitive decline was found to correlate with the neuropathological stages of PD, suggesting that the risk to develop dementia increases with disease progression [60].…”
Section: Mouse Models Of Predominant Brainstem Cortico/subcortical-limentioning
confidence: 55%
“…These deficits are primarily observed in the attentional and executive domains [16,17]. As disease progresses, a subset of patients develops severe cognitive deficits leading to dementia [18,19]. A main risk factor for the development of severe cognitive deficits in PD is age, but the presence of early cognitive deficits may also increase the risk of later, more severe, cognitive symptoms [20,21].…”
Section: Introductionmentioning
confidence: 99%